KEPEMIMPINAN KEPALA DESA DALAM MENINGKATKAN PARTISIPASI MASYARAKAT DI DESA KOLAM - Syahilla Azzahra; Browin Christmas Ginting; Teresia Vredemika Sidauruk; Nayla Azizah (STKIP Subang, 2025)
This study aims to analyze the role of village head leadership in increasing community participation in Kolam Village, Percut Sei Tuan District, Deli Serdang Regency. The village head plays an important role as a facilitator, motivator, and driving force in optimizing residents’ participation in village development. This research uses a qualitative approach with a case study method, through observation and interviews with the village head, village officials, community leaders, and residents.The results show that the village head of Kolam Village applies a participatory leadership style, as reflected in the regular deliberation meetings, community service activities, health programs, and socio-religious events that actively involve the community. Communicative, transparent, and inclusive leadership has proven to increase residents’ trust and motivation to participate in development. However, there are still challenges such as limited communication and delays in village fund disbursement, which hinder full participation.This study concludes that effective, open, and community-empowerment-oriented village head leadership is the key to realizing participatory and sustainable village development.